Venom variation and ontogenetic changes in the Crotalus molossus complex: insights into composition, activities, and antivenom neutralization - Miguel, Borja (2025)
The Crotalus molossus complex consists of five to seven phylogenetically related lineages of black-tailed rattlesnakes widely distributed in Mexico. While previous studies have noted venom variation within specific lineages of the Crotalus molossus complex, a comprehensive characterization of interspecific and ontogenetic venom variations, their functional implications, and the neutralizing ability of the Mexican antivenom against these variants remains largely unexamined. Herein, using two proteomic approaches for five lineages (C. basiliscus, C. m. molossus, C. m. nigrescens, C. m. oaxacus, and C. ornatus) of the C. molossus complex we characterized the number of toxins and their relative abundance in the venom of individuals of varying sizes. All five lineages undergo ontogenetic venom composition shifts associated with snake length. However, the pattern of ontogenetic shifts varied among lineages. In some lineages, these shifts led to significant differences in proteolytic, phospholipase A2, and fibrinogenolytic activities. Venom in smaller C. basiliscus, C. m. nigrescens, and C. m. oaxacus individuals had lower LD50 values (more lethal) in mice. Whereas the venom lethality of C. m. nigrescens (both juvenile and adult) and C. m. oaxacus (adult) was several times higher in a mammalian (mouse) model than in a reptilian (iguana) model. Antivipmyn® showed different neutralizing potencies toward venom pools. Overall, our results indicated that even among closely related rattlesnake lineages, venom phenotypes may vary greatly, impacting their function and the efficacy of antivenom neutralization.